Revision of the genus Dziriblatta Chopard, 1936 (Blattodea, Ectobiidae, Ectobiinae). III. The species of the subgenus Dziriblatta - Bohn, Horst (Zootaxa, 2021)
The present paper is the third part of a revision of the genus Dziriblatta and treats the nominal subgenus Dziriblatta and its species. The subgenus contains 10 species of which 8 are new to science. The species can be distributed to two species groups: the bolivari-species group with Dz. (Dz.) algerica, Dz. (Dz.) bolivari, Dz. (Dz.) brevisacculata, spec. nov., Dz. (Dz.) curvisetosa, spec. nov., and Dz. (Dz.) pilleata, spec. nov.—and the lobososacculata-species group with Dz. (Dz.) altotuberculata, spec. nov., Dz. (Dz.) lobososacculata, spec. nov., Dz. (Dz.) planotuberculata, spec. nov., Dz. (Dz.) ramososacculata, spec. nov., and Dz. (Dz.) undulata, spec. nov.. The descriptions of the species are complemented by numerous images showing their most important structures, their distribution in southern Spain and Morocco, and their supposed phylogenetic relationships. A determination key allows the discrimination of the males.